A Missense Mutation in a Large Subunit of Ribonucleotide Reductase Confers Temperature-Gated Tassel Formation. Issue 4 (5th October 2020) - Xie, Shiyi; Luo, Hongbing; Huang, Yumin; Wang, Yaxin; Ru, Wei; Shi, Yunlu; Huang, Wei; Wang, Hai; Dong, Zhaobin; Jin, Weiwei
Abstract : Temperature - dependent shoot apical meristem development is conferred by temperature - gated physical interactions between ribonucleotide reductase subunits . Abstract: Temperature is a major factor regulating plant growth. To reproduce at extreme temperatures, plants must develop normal reproductive organs when exposed to temperature changes. However, little is known about the underlying molecular mechanisms. Here, we identified the maize ( Zea mays ) mutant thermosensitive vanishing tassel1 - R ( tvt1 - R ), which lacks tassels at high (restrictive) temperatures due to shoot apical meristem (SAM) arrest, but forms normal tassels at moderate (permissive) temperatures. The critical stage for phenotypic conversion in tvt1 - R mutants is V2 to V6 (Vn, where "n" is the number of leaves with collars visible). Positional cloning and allelism and complementation tests revealed that a G-to-A mutation causing a Arg277 -to-His277 substitution in ZmRNRL1, a ribonucleotide reductase (RNR) large subunit (RNRL), confers the tvt1 - R mutant phenotype. RNR regulates the rate of deoxyribonucleoside triphosphate (dNTP) production for DNA replication and damage repair. By expression, yeast two-hybrid, RNA sequencing, and flow cytometric analyses, we found that ZmRNRL1- tvt1 - R failed to interact with all three RNR small subunits at 34°C due to the Arg277 -to-His277 substitution, which could impede RNR holoenzyme (α2 β2 ) formation, thereby decreasing the dNTP supply for DNA replication. Decreased dNTP supply may be especially severe for the SAM that requires a continuous, sufficient dNTP supply for rapid division, as demonstrated by the SAM arrest and tassel absence in tvt1 - R mutants at restrictive temperatures. Our study reveals a novel mechanism of temperature-gated tassel formation in maize and provides insight into the role of RNRL in SAM maintenance.